Calculation of critical endpoints and phase diagrams of highly asymmetrical binary mixtures - Sánchez, Francisco Adrián (2023)
The determination of monovariant lines like critical and three-phase equilibrium curves in phase diagrams of binary mixtures plays a fundamental role in analyzing potential process conditions and assessing the qualitative and quantitative capabilities of thermodynamic models. In this regard, the automatic generation of global phase equilibrium diagrams (GPED) has become an invaluable analytical tool, enabling intelligent solutions to highly complex and nonlinear mathematical problems. In particular, it was mainly the software GPEC (Global Phase Equilibrium Calculations) and the publications describing its computation strategies and methods that made it possible for a large international community of researchers to use GPED’s as frequent tools in the application of equations of state to different problems.However, the original GPEC algorithm face challenges in resolving highly asymmetric mixtures, such as gases (CH4, C2H6, CO2, N2) in combination with heavy paraffins, vegetable oils, or even polymers, as well as electrolytic aqueous systems. These challenges manifest in convergence problems and floating point overflow. More specifically, the UCEP or “k point” located quite close to the pure gas critical point (phase behavior of type III or IV) frequently fails to be properly found and converged in this type of systems due to the low concentration of the solute in the critical phase.In this study, we present an innovative calculation methodology to address these challenges in highly asymmetric binary systems. Our approach builds upon the extension of existing algorithms, aiming to achieve an automatic generation of GPED that does not require manual intervention. The approach is based on the formulation of other phase equilibrium problems dealing with nearly pure phases. As a case study, we apply our methodology to analyze phase equilibrium transitions in industrially relevant systems, such as CO2 with heavy alkanes.